2019
DOI: 10.1155/2019/2735492
|View full text |Cite
|
Sign up to set email alerts
|

Moxibustion Exerts a Neuroprotective Effect through Antiferroptosis in Parkinson’s Disease

Abstract: The objective of this study was to explore the neuroprotective effect of moxibustion on rats with Parkinson’s disease (PD) and its mechanism. A Parkinson’s disease model was established in rats using a two-point stereotactic 6-hydroxydopamine injection in the right substantia nigra (SN) and ventral tegmental area. The rats received moxibustion at the Baihui (GV20) and Sishencong (EX-HN1) acupoints for 20 minutes, six times a week, for 6 weeks. The right SN tissue was histologically and immunohistochemically ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 46 publications
(46 reference statements)
1
23
0
Order By: Relevance
“…TFR1 transports iron from the extracellular environment into cells, facilitating the cellular iron pool essential for ferroptosis ( 14 ). FTH1 is a major iron storage protein responsible for maintaining the iron balance in cells ( 15 ). Ferroptosis is implicated in ischemic stroke ( 4 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…TFR1 transports iron from the extracellular environment into cells, facilitating the cellular iron pool essential for ferroptosis ( 14 ). FTH1 is a major iron storage protein responsible for maintaining the iron balance in cells ( 15 ). Ferroptosis is implicated in ischemic stroke ( 4 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…PD was established in the rats as previously described ( 15 ). Briefly, the rats were anesthetized (100 mg/kg ketamine and 10 mg/kg xylazine, intraperitoneal injection) and placed in a stereotaxic apparatus with the skull flat.…”
Section: Methodsmentioning
confidence: 99%
“…Fe 2+ release and ferritin degradation are associated with cell dysfunction through the process of ferritinophagy, causing ROS formation and lipid peroxidation by releasing iron at sufficient levels, triggering ferroptosis ( 13 ). In previous studies, the authors demonstrated that was involved in ferroptosis in in vivo and in vitro models of Parkinson's disease (PD) ( 14 , 15 ). Therefore, it is of considerable interest to explore the upstream molecules targeting FTH1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TFR1 transported iron from extracellular environment into cells, facilitating the cellular iron pool essential for ferroptosis [13]. FTH1 is a major iron storage protein responsible for maintaining the iron balance in cells [14]. Ferroptosis has been reported to influence NF-κB/NLRP3 inflammasome signaling, and is implicated in ischemic stroke [15,16].…”
Section: Introductionmentioning
confidence: 99%